Impact of COVID-19 on Formal Education: An International Review of Practices and Potentials of Open Education at a Distance - Stracke, Christian M.; Sharma, Ramesh Chander; Bozkurt, Aras; Burgos, Daniel; Swiatek Cassafieres, Cécile; Inamorato dos Santos, Andreia; Mason, Jon; Ossiannilsson, Ebba; Santos-Hermosa, Gema; Shon, Jin Gon; Wan, Marian; Agbu, Jane-Frances Obiageli; et al. (International Review of Research in Open and Distributed Learning, 2022)
In terms of scale, shock, and disenfranchisement, the disruption to formal education arising from COVID-19 has been unprecedented. Anecdotally, responses from teachers and educators around the world range from heightened caution to being inspired by distance education as the “new normal.” Of all the challenges, face-to-face and formal teaching have been most heavily affected. Despite some education systems demonstrating resilience, a major challenge is sustaining quality and inclusiveness in formal education suddenly delivered at a distance. In probing these issues, this article profiles international perspectives on the role of open education in responding to the impact on formal school and higher education caused by the COVID-19 pandemic. We proceed by highlighting and analysing practices and case studies from 13 countries representing all global regions, identifying and discussing the challenges and opportunities that have presented themselves. Reports cover the period from the beginning of 2020 until 11 March 2021, the first anniversary of the COVID-19 outbreak as declared by the World Health Organization. In our comparative study, we identify seven key aspects of which three (missing infrastructure and sharing OER, open education and access to OER, and urgent need for professional development and training for teachers) are directly related to open education at a distance. After comparing examples of existing practice, we make recommendations and offer insights into how open education strategies can lead to interventions that are effective and innovative—to improve formal education at a distance in schools and universities in the future.